Study of Characteristics of Samosir Panorusan Goat in Samosir District - Alan Parulian Tampubolon; Maruf Tafsin; Sayed Umar (Randwick International of Social Science Journal, 2023)
This study aims to determine Panorusan Samosir goat’s characteristics in Samosir district. The method used in this research is the observation method. The sampling technique was purposive sampling, namely 64 samples consisting of 7 males goat, 30 broodstock, 20 female lamb, 9 male lamb for quantitative traits while 264 qualitative traits. The data collected are quantitative characteristics including: body weight, body length, shoulder height, chest circumference, chest width, chest depth and ear length while for qualitative characteristics include: coat color, ear shape, horn color and nail color of Panorusan Samosir goats in the district Samosir. The data that has been collected was analyzed using the T-test. The average value of the quantitative characteristics of Panorusan Samosir goats was analyzed using the T2-hoteling statistical test, then principal component analysis was used to identify quantitative traits in goats. Data processing was assisted by using statistical software SPSS 20. The results showed that gender did not affect the quantitative characteristics of the Panorusan Samosir goats, while for the qualitative characteristics, namely the color of the coat was still dominated by white (57.44%), the shape of the ears was erect (72, 92%), the color of the horns is dominated by white (69.32%), and the color of the nails is also dominated by white (79.17).